Karakteristik es krim susu beras dengan perbedaan penambahan emulsi putih telur dan waktu mixing - Cahyaning Rini Utami; Luluk Nur Aini Mufidah (TEKNOLOGI PANGAN : Media Informasi dan Komunikasi Ilmiah Teknologi Pertanian, 2026)
Rice milk ice cream is an alternative lactose-free frozen product, but its texture and stability are greatly influenced by the dough's ability to form an emulsion and trap air during churning. This study aimed to evaluate the effect of egg white concentration as an emulsion and mixing time on the physicochemical characteristics and organoleptic acceptability of rice milk ice cream. The study used a two-factorial Randomized Block Design: 50, 100, and 150 g of egg white and 10 and 20 minutes of mixing time (6 combinations; 3 replications). Physicochemical parameters included overrun, melting time, fat, water, and ash content, while organoleptic tests (taste, color, texture) were assessed by 25 untrained panelists. Physicochemical data were analyzed using ANOVA followed by Tukey's test, and organoleptic data were analyzed using Friedman's test; the best treatment was determined using the De Garmo Effectiveness Index. Key findings are: Higher egg white concentration and longer mixing time increased overrun, melting time, and fat, water, and ash content. The optimal treatment (150 g egg white, 20 minutes mixing) resulted in 13.70% overrun, 114.34 seconds melting time, 8.07% fat, 79.36% moisture, 2.52% ash, and hedonic scores of 4.00 (taste), 3.82 (color), and 4.20 (texture). The enhanced emulsion improved ice cream lightness and softness (overrun) and slowed melting, but the increased moisture content indicates that further research is needed to optimize stabilizers and sweeteners for consistent quality.